Lipid Nanoparticles Deliver mRNA to the Brain after an Intracerebral Injection - Tuma, Jan; Chen, Yu-Ju; Collins, Michael G; Paul, Abhik; Li, Jie; Han, Hesong; Sharma, Rohit; Murthy, Niren; Lee, Hye Young (Biochemistry (Easton), 2023)
Neurological disorders are often debilitating conditions with no cure. The majority of current therapies are palliative rather than disease-modifying; therefore, new strategies for treating neurological disorders are greatly needed. mRNA-based therapeutics have great potential for treating such neurological disorders; however, challenges with delivery have limited their clinical potential. Lipid nanoparticles (LNPs) are a promising delivery vector for the brain, given their safer toxicity profile and higher efficacy. Despite this, very little is known about LNP-mediated delivery of mRNA into the brain. Here, we employ MC3-based LNPs and successfully deliver Cre mRNA and Cas9 mRNA/Ai9 sgRNA to the adult Ai9 mouse brain; greater than half of the entire striatum and hippocampus was found to be penetrated along the rostro-caudal axis by direct intracerebral injections of MC3 LNP mRNAs. MC3 LNP Cre mRNA successfully transfected cells in the striatum (∼52% efficiency) and hippocampus (∼49% efficiency). In addition, we demonstrate that MC3 LNP Cas9 mRNA/Ai9 sgRNA edited cells in the striatum (∼7% efficiency) and hippocampus (∼3% efficiency). Further analysis demonstrates that MC3 LNPs mediate mRNA delivery to multiple cell types including neurons, astrocytes, and microglia in the brain. Overall, LNP-based mRNA delivery is effective in brain tissue and shows great promise for treating complex neurological disorders.
Keywords: malá interferující RNA; nanočástice; myši; Animals; nemoci nervového systému; Nanoparticles; vodící RNA, systémy CRISPR-Cas; Nervous System Diseases; mozek; Mice; zvířata; RNA, Guide, CRISPR-Cas Systems; Brain; RNA, Messenger; RNA, Small Interfering; messenger RNA